Sedimentation Dynamics of a Small Hill Forest Catchment in Ulu Langat, Selangor, Malaysia - Detphachanh, Soulisack (2000)
This study assesses the sedimentation dynamics of a small hill forest catchment with an area of 2.6 km² in Ulu Langat Forest Reserve, Selangor, Malaysia. The study catchment was equipped with rainfall and water level recorder to assess the hydrological characteristics of the area. The annual rainfall data recorded during the study period from July 1997 to June 1998 was 2051.6 mm. The maximum monthly rainfall of 431.4 mm was recorded in October 1997 while the minimum of 25.1 mm occurred in February 1998. In October-December of 1997 and May-June of 1998, high rainfalls were observed due to inter north-east monsoon and transition monsoon respectively. Sedimentation dynamics in the study area was evaluated using the Helley-Smith bed load sampler and a two-weekly survey of stored sediment. Bed load was estimated using a bed load-rating curve and discharge time interval of half-hourly, hourly and daily mean values, there are the annual bed load was 4.61, 4.46 and 3.81 t respectively which presented about 17.0% of the total load. Sediment deposition measurement was conducted fortnightly over a year showed the high sediment transported during two storms events. The sediment deposited about 3.064 t and 2.033 t during of 19 October to 1 November 1997 and 14 - 27 June 1998, compared with the annual load of 11.36 t, for the study period were transported. The bed load particle size distribution is measured in order to determine the quality of the sediment transported. A wide range of particle size was observed. This ranged from 0.05 to 0.9 mm at D₅, 0.35 to 3.1 mm at D₅₀ and 0.75 to 5.1 mm at D9S with average of 0.24, 1.1 and 2.16 mm, respectively. Sedimentation dynamics was evaluated based on the bed load and sediment storage in the Sg. Pangsun watershed. High sediment loads were transported during storms, the proportion of the bed load and sediment storage load was year total: bed load versus sediment storage.